Autonomy and trust in professional ethics - Millett, Stephan; Tapper, Alan (Australian Association of Professional and Applied Ethics, 2009)
This paper examines recent discussions of the key ideas of autonomy and trust in the professional ethics literature. We argue that while there is a consensus on the nature of professions and professional ethics, there is no agreement on the philosophical basis of this consensus. Some authors, most notably in the bioethics field, derive professional ethics from general philosophical ethics. We argue that these derivations have so far been flawed, since any general ethics must apply equally to both professional and client, and thus it is difficult to see how the special obligations of professionals are grounded. We don't offer any solution to this problem, just a diagnosis of it.